Analysis of Total Harmonic Distortion in Inverter Systems: A Comparative Study of Square Wave, Phase Shift and Multilevel Inverters - Othman, Mohamed Faizal; Abu Bakar, Afarulrazi (Journal of Electronic Voltage and Application, 2025)
This study investigates the total harmonic distortion (THD) in inverter systems, comparing square wave, phase shift, and multilevel inverters. The performance of inverters is crucial for efficiently converting direct current (DC) to alternating current (AC), especially in renewable energy applications and electric vehicles. The research identifies gaps in understanding THD performance across different inverter configurations under various input conditions and modulation techniques. Utilizing MATLAB/Simulink, the study simulates a proposed multilevel inverter's output voltage characteristics in both filtered and unfiltered scenarios. The objectives include stimulating THD performance under square wave inputs, SPWM and phase shifts while analyzing the multilevel inverter's output voltage. Findings aim to enhance inverter designs for better power quality and efficiency, highlighting multilevel inverters' advantages over traditional two-level inverters. The implications of filtering techniques on voltage quality are also discussed, contributing valuable insights to the field of power electronics.